Pengaruh Kepemilikan Institusional, Komisaris Independen, Komite Audit, Pertumbuhan Penjualan, dan Leverage terhadap Manajemen Laba - Yola Fionita; Halkadri Fitra (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect to institusional ownership, independent commissioners, audit commites, sales growth, and leverage on earnings management. The population used ini this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study were 40 companies using purposive sampling method. Hypothesis testing in this study uses multiple linear regression analysis.The result of this study indicate that institusional ownership, audit committee, sales growth, and leverage have no effect on earnings management, while independent commissioners affect earnings management. Simultaneously institusional ownership, independent commissioners, audit committees, sales growth, and leverage affect earnings management.